2023
DOI: 10.1186/s12934-023-02116-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extracellular production of raw starch-degrading α-amylase in Bacillus subtilis through expression regulatory element modification and fermentation optimization

Abstract: Background Raw starch-degrading α-amylase (RSDA) can hydrolyze raw starch at moderate temperatures, thus contributing to savings in starch processing costs. However, the low production level of RSDA limits its industrial application. Therefore, improving the extracellular expression of RSDA in Bacillus subtilis, a commonly used industrial expression host, has great value. Results In this study, the extracellular production level of Pontibacillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…According to the existing literature, the enzymes of utmost significance in biocatalysis include lipases, laccases, cellulases, glucosidases, and amylases [ 37 , 38 ].…”
Section: Upstream Bioprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the existing literature, the enzymes of utmost significance in biocatalysis include lipases, laccases, cellulases, glucosidases, and amylases [ 37 , 38 ].…”
Section: Upstream Bioprocessingmentioning
confidence: 99%
“…The noteworthy outcomes revealed that, after fine-tuning the gene expression regulator, signal peptide promoter sequences, and the ribosome binding site (RBS) upstream of the amyZ1 gene, an astonishing enzyme activity of 2.6 times greater than that of the native enzyme was achieved, totaling an impressive 4824.2 U/mL. Moreover, through a rigorous optimization process for the carbon and nitrogen sources, a remarkable α-amylase activity of 49,082.1 U/mL was attained within a 3 L fermenter [ 37 ].…”
Section: Upstream Bioprocessingmentioning
confidence: 99%
See 1 more Smart Citation